Utilization of Smartphones for Accessing Agricultural Information by Farmers in Bokaro District of Jharkhand (Indian Journal of Extension Education, 2025)
The study examines the utilization pattern of smartphones for accessing agricultural information among farmers in Bokaro district of Jharkhand. A total of 160 respondents were selected through a multistage sampling method across sixteen villages. Data were collected using a pre-tested interview schedule to assess the frequency, purpose, and extent of smartphone usage during 2024-25. The results revealed that the majority of farmers regularly used smartphones to access weather forecasts, market prices, and pest management information. However, usage was relatively low for advanced topics such as post-harvest practices, webinars, and online agricultural forums. The overall utilization index indicated moderate use, with 73.13 per cent of respondents falling in the medium category. Kruskal– Wallis H test showed significant differences in smartphone utilization based on education, occupation, landholding, income, and knowledge level. Correlation analysis identified annual income and knowledge as the most influential factors. Respondents with higher income and knowledge were significantly more inclined to use smartphones for agricultural purposes. In contrast, variables like age, family size, and scientific orientation showed no significant influence. The study highlights the growing role of digital tools in rural agriculture and emphasizes the need for targeted interventions to enhance digital literacy and bridge the information gap among farmers.